The resurrection of Zachary Wheeler - Wynn, Bob; Nielsen, Leslie, 1926-2010; Madison Productions Incorporated; Cinetel Films ([Madison, WI] : Madison Productions, Inc., 1971)
A U.S. Senator is spirited away to a secret New Mexico medical lab after a serious car crash. His injuries are completely healed by a secret organization that has developed advanced medical technology. What does the organization want in exchange for saving his life? Meanwhile, a reporter who witnessed the accident decides to investigate the senator's disappearance. --
Leslie Nielsen, Bradford Dillman, James Daly, Angie Dickinson, Robert J. Wilke, Jack Carter.
Cinematographer, Bob Boatman; editor, Jerry Greene; music, Marlin Skiles.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Human cloning -- Drama; Made-for-TV movies; Science fiction films; Thrillers (Motion pictures); Feature films; Internet videos; Streaming video